Effect of Normosil Probiotic Supplementation on the Growth Performance and Blood Parameters of Broiler Chickens - Khabirov, Airat; Khaziakhmetov, Fail; Kuznetsov, Vyacheslav; Tagirov, Hamit; Rebezov, Maksim; Andreyeva, Aleksandra; Basharov, Almaz; Yessimbekov, Zhanibek; Ayaz, Muhammad (Indian Journal of Pharmaceutical Education and Research, 2020)
Purpose: This study was aimed to investigate the effects of probiotic “Normosil” containing a mixture of living cultures of Lactobacillus and Enterococcus strains at a concentration of 1×106 and 1×107 CFU/mL was assessed. Materials and Methods: Effect of Normosil on the growth performance, hematological and biochemical factors of Arbor Acres broilers from a day-old to 42-day old (n= 175, 1 control + 4 experimental groups) daily and periodically. Results: Results showed that Normosil (1×106 CFU/mL) had a relatively better growth performance and showed an increase in the average daily growth by 10.6%-13.0% compared to control. In comparison to control, broilers provided with daily and periodic dose of Normosil showed an increase in the level of blood erythrocytes by 5.6% and 14.1% after 21 days, respectively; and an increase in hemoglobin, glucose, total protein, albumin, sodium, potassium and calcium by 4.9% and 10.9%,12.3% and 17.4%,0.5% and 5.7%, 3.7% and 14.4%, 2.1% and 5.0, 17.0% and 33.3% and 7.7% and 21.2% (p<0.05), respectively after 42 days of growth. Nutrient digestibility in context to organic matter, raw protein, raw fat and nitrogen-free extractive compounds in broilers fed with periodic and daily doses of Normosil (106 CFU/mL) was higher than in control by 4.4%-6.6%, 2.5%-6.2, 1.6%-5.5% and 8.2%-12.2%, respectively. Compared to control, the femoral muscles had a higher protein content of 6.0% and 15.7% (experimental groups III and IV); low carcass fatness by 8.1% (group IV); and low content of connective tissue. Conclusion: This study suggests the potential benefits of Normosil supplementation for improving the growth and quality of broilers.
Keywords: Probiotics; Biochemical parameters; ArborAcres cross broilers; Normosil; Hematological parameters; Albumin-globulin coefficient; Nutrient digestibility